2019
DOI: 10.1038/s41598-019-47280-8
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variants of renal veins: A meta-analysis of prevalence

Abstract: The main aim of this article is to establish the actual prevalence of renal vein variations (circumaortic renal vein, retroaortic renal vein, double renal vein), and to increase awareness about them. To this purpose, we have performed a meta-analysis of prevalence, using the MetaXL package, We included 105 articles in the final analysis of prevalence, of which 88 contained data about retroaortic renal vein, 84 – about circumaortic renal vein, and 51 - about multiple renal veins. The overall prevalence for retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 89 publications
1
49
0
1
Order By: Relevance
“…8,10,45 Outside of the field of transplantation, it has been shown that right kidneys are overall more likely to have multiple renal veins. 60 This could contribute to the increased anastomosis time and the increase in technical complications. Unfortunately, no studies performed multivariate analyses which adjusted for this potential confounder.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,45 Outside of the field of transplantation, it has been shown that right kidneys are overall more likely to have multiple renal veins. 60 This could contribute to the increased anastomosis time and the increase in technical complications. Unfortunately, no studies performed multivariate analyses which adjusted for this potential confounder.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of multiple renal veins has been investigated in anatomical studies and by CT angiography [ 1–5 ]. In a meta-analysis of 105 studies, the mean incidence of multiple renal veins was 16.7% [ 1 ]. Multiple renal veins were much more common on the right (16.5%) than on the left side (2.1%).…”
Section: Discussionmentioning
confidence: 99%
“…So sind auch Mehrfachanlagen anzutreffen und zirkumaortale Verläufe. Dabei ist die rechtsseitige Nierenvene variantenreicher als die linksseitige [12,13].…”
Section: Proximales Gefäßsegment: Gonadale Venen Und Nierenvenenunclassified